1996
DOI: 10.5144/0256-4947.1996.90
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus in Saudi Patients Admitted to Hospital with Bronchiolitis: Use of Direct Fluorescent Antibody Tests as a Rapid Diagnostic Tool

Abstract: : [90][91][92] Bronchiolitis is a major cause of morbidity and occasional mortality in young infants and children all over the world. Respiratory syncytial virus (RSV) is the major etiologic agent responsible for this condition. The illness is more severe in patients with bronchopulmonary dysplasia and congenital heart diseases, especially with pulmonary hypertension and preterm infants. Early treatment with ribavirin is recommended in infants with underlying immunodeficiency and complicated heart disease (inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Other investigations reported 80-88% of bronchiolitis due to RSV in children less than 6 months of age [32,38]. Another study also confirmed that RSV was mostly associated with bronchiolitis in the pediatric patients from this region [37].…”
Section: Clinical Symptoms Associated With Rsv Infectionmentioning
confidence: 58%
See 1 more Smart Citation
“…Other investigations reported 80-88% of bronchiolitis due to RSV in children less than 6 months of age [32,38]. Another study also confirmed that RSV was mostly associated with bronchiolitis in the pediatric patients from this region [37].…”
Section: Clinical Symptoms Associated With Rsv Infectionmentioning
confidence: 58%
“…Fifty four percent of the cases were positive for RSV [36]. Another study included ALRI patients less than 2 years of age and detected RSV in 70% of the samples by DFA and culture [37]. RSV accounted for 79% of the ALRI cases (less than 5 years of age) in hospitalized children in another study from Riyadh during 1993-96 [38].…”
Section: Prevalence Of Rsvmentioning
confidence: 96%
“…8 Another study conducted in Riyadh, which included 485 ALRI patients under the age of 2, detected RSV in 70% of the samples. 9 RSV accounted for 79% of the total 1429 ALRI cases in children under the age of 5 who were hospitalized in another study from Riyadh between 1993 and 1996. 10 Out of 256 sample cases hospitalized with 11 In the case of children admitted for ALRI from Abha during 1997-2001, RSV was found to be positive in 40% of the 51 cases.…”
mentioning
confidence: 98%